Attachment Style and Conflict Resolution Strategies among Married Couples in the Light of Some Demographic Variables - Kassem, Abd El. Mureed Abd El Gaber; Alkousy , Ahmed Moustafa Mohamed Ahmed; Yamani, Ibrahim bin Abdul Jalil; Moussa, Yasser Mohamed Elsayed (Journal of Ecohumanism, 2024)
This study aims to specify relations between Conflict Resolution Strategies, adult attachment style in a sample of married couples. It also aims to find out the role of attachment styles in predicting conflict resolution strategies the sample consists of (203) males, and females, the researcher used attachment scale, conflict resolution strategies questionnaire-) Kurdek1994. The findings of the study reveal that there is a statistically significant relationship between conflict resolution strategies and all attachment styles. The results also show that there is predictive ability of the attachment styles to Conflict Resolution Strategies.